BAGELEN PASCA PERANG JAWA (1830-1950): Dinamika Sosial Politik dan Ekonomi di Bekas Wilayah Negaragung Kasultanan Mataram Islam (Vorstenlanden) - Himayatul Ittihadiyah (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2012)
This paper aims at describing one of the Javanese Islam which is sociopoliticallyand economically may be cited as the most dynamic regions duringthe period of one century. Bagelen, the former territory